The Role of Traditional Mantir in Resolving Muslim Dayak Household Disputes in the East Kotawaringin Regency - Khair, Abdul; Mualimin Mualimin; Surya Sukti; Munib Munib (Nurani: jurnal kajian syari’ah dan masyarakat, 2025)
This study is grounded in the socio-cultural context of Muslim Dayak communities living in the rural and geographically isolated regions of Kotawaringin Timur Regency. They prefer to resolve disputes through the mantir custom rather than going through formal channels in the Religious Court. This study aims to analyze the role of mantir adat in resolving domestic disputes within the Muslim Dayak community and to identify the reasons behind their preference for customary mechanisms over religious courts, which are perceived as less efficient, costly, and less in harmony with local values. This research adopts an empirical methodology with a socio-legal approach, focusing on the local norms and customary practices within the Regency of Kotawaringin Timur. Findings show that the public more often chooses custom mantir because the procedure is considered simpler, requires no legal skills or help from an advocate, is closer in a geographical sense, and incurs no high costs. Additionally, the custom mantir service is flexible and available when needed. The findings underscore the critical role of customary functionaries in facilitating the resolution of communal disputes through a synergistic framework, in alignment with national legal mandates.